Implementation of Assimilation in the Progressive Law Perspective: Toward a Humane and Beneficial Society - Riko Hamdan; Helmi; Meri Yarni (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The overcapacity of correctional institutions in Indonesia has led to various complex humanitarian, legal and social problems. One of the solutions pursued by the government is the assimilation policy, which aims to reduce the capacity burden while encouraging the social reintegration of prisoners. However, the implementation of this policy is often trapped in a legalistic-formal approach that ignores aspects of substantive justice. This article examines the implementation of the assimilation policy in the perspective of progressive law, which places law as a means of social transformation, not merely a normative rule. Through normative legal research methods with statutory, conceptual, and philosophical approaches, this article finds that the progressive legal approach plays an important role in encouraging assimilation policies that are more humanist, inclusive, and just. Progressive law emphasizes the importance of rehabilitation, community participation, and protection of prisoners' rights as part of the development process. In addition, concrete support is needed in the form of job training programs, psychosocial assistance, and fair and transparent supervision. By emphasizing the principles of justice, humanity and social benefit, the implementation of progressive law-based assimilation can reduce stigma against prisoners and create a more dignified correctional system. The results show that the success of the assimilation policy is greatly influenced by the synergy between an adaptive legal approach and strong social participation. In conclusion, progressive law can be an effective foundation for reforming correctional policies to be more oriented towards recovery, not just punishment